P.S. Think of it like this. Even functions represent a positive number. Odd functions represent a negative number.

Even Function

Then f(x)g(x) = (f*g)(x) = f(-x)g(-x) = (f*g)(-x)

(f*g)(x) = (f*g)(-x)

But positive by negative provides a negative result. (odd)

Source(s): XPressTutor.com

(f*g)(x) = f(x)g(x) = f(-x)*g(-x) =/= -f(-x)*g(-x) = -(f*g)(-x)

(f*g)(x) =/= -(f*g)(-x)

1. Even

2. Even

3. Odd

–

P.S. Think of it like this. Even functions represent a positive number. Odd functions represent a negative number.

To sum it up,

1)even

2) even

3) odd.

To sum it up,

1)even

2) even

3) odd.

–

Source(s): XPressTutor.com

Even Function

P.S. Think of it like this. Even functions represent a positive number. Odd functions represent a negative number.

1. Even

2. Even

3. Odd

1. Even

2. Even

3. Odd

Even Function

This post is last updated on hrtanswers.com at Date : 1st of September – 2022